FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENGOBATAN PADA PASIEN TUBERKULOSIS PARU DI PUSKESMAS TANJUNGSARI KABUPATEN BOGOR TAHUN 2020 - Putri Fazartika Santoso (2020)
Tuberculosis is an infectious disease that caused by Mycobacterium Tuberculosis. Indonesia is the country with the 3rd highest Tuberculosis burden in the world. The success rate of treatment in Indonesia in 2018 was 364,197 (84.59%) and the treatment success rate was at least 90.0%. The purpose of this study was to analyze the factors that affecting the success of treatment in pulmonary tuberculosis patients in Puskesmas Tanjungsari, Bogor District. This study used an observational analytic design, using a comparative study and using the help of the Morisky Medication Adherence Scale (MMAS-8) and Physical Activity Scale for the Elderly (PASE). The study involved 59 respondents, and used purposive sampling technique. Logistic regression analysis showed gender (p=0.018), profession (p=0.048), social economy (p=0.043), education (p=0.017), obedience (0.024) and PMO (p=0.037) had a significant effect (p <0.05) on the success of tuberculosis treatment. The closer distance of residence (OR=613,463, CI95%=0.019-19903940,743), with the presence of PMO (OR=368,638, CI95%=1,433-94807,660), the higher of education (OR=67,976, CI95%=2,101-2199,788), attitude (OR=2,584, CI95%= 0,167-39,945) and treatment obedience (OR=17,263, CI95%=1,450-205,470), will increase the success of pulmonary tuberculosis treatment at Puskesmas Tanjungsari.